Reducing soft tissue artefacts through projection of markers and microwave imaging: An exploratory study - Vignesh Radhakrishnan; Martin Robinson; Niccolo M. Fiorentino; Samadhan B. Patil; Adar Pelah (Scientific Reports)
Abstract Soft tissue artefacts (STA) are widely considered the most critical source of error in skin-mounted marker-based biomechanics, negatively impacting the clinical usability of skin-mounted marker-based data. Amongst the numerous solutions proposed to ameliorate STA, incorporating true bone movement—acquired using adaptive constraints, projection of markers, or various imaging modalities—has been reported to improve kinematic accuracy. However, efficacy of these proposed solutions reduces for different investigated motions and participants. In this study, we propose two novel marker projection schemes, wherein a cluster of markers are projected onto the bone surface during motion. Additionally, we investigate the feasibility of applying a novel, safe and cost-effective imaging modality—microwave imaging—to detect the location of the bone from the skin surface. Our results indicate that the novel marker projection schemes reduce kinematic errors significantly (by 50%) and improve the quality of computed kinematics (95% correlation to true bone movement). In addition, our results show that microwave imaging was able to detect the bone from the skin surface in both male and female anatomical models of varying body mass index scores and poses. We believe our findings underscore the generalisability and applicability of our proposed solution to reduce STA.